  Question:

2$^{73}$ - 2$^{72}$ - 2$^{71}$ is same as

• A

2$^{69}$

• B

2$^{70}$

• C

2$^{71}$

• D

2$^{72}$

Posted by: A. S. on 14.11.2017 Bodhoday from Howrah
• Like

2^(73) – 2^(72) – 2^(71)

= 2^(71) x {2^(2) – 2^(1) – 1}

=2^(71) x (4 – 2 – 1)

=2^(71) x (1)

=2^(71) Suhrita S. from Kolkata
• Like

V
Vishnu T. from Delhi
• Like

hi , best trick , take lowest power common & then proceed.

2^71( 2^2-2^1-1)=2^71(4-2-1)=2^71 Dibyendu M. from Kolkata
• Like

Take an example

2 ^5 - 2^4 = 2x2x2x2x2 - 2x2x2x2x = 32-16 = 2^4

Hence 2^73 - 2^72 = 2^72

Now 2^72 - 2^71 = 2^71

Hence correct option is C = 2^71   Ans

V
Vijay G. from Mumbai
• Like

ANS--C

2^(73) – 2^(72) – 2^(71)

= 2^(71) x {2^(2) – 2^(1) – 1}

=2^(71) x (4 – 2 – 1)

=2^(71) x (1)

=2^(71)

S
Seemant S. from Delhi
• Like ### Post Answer and Earn Credit Points

Get 5 credit points for each correct answer. The best one gets 25 in all.

Similar Questions
Topic Cloud

## Need a Tutor or Coaching Class?

Post an enquiry and get instant responses from qualified and experienced tutors.

Post Requirement

Drop Us a Query